2022
DOI: 10.1002/adma.202204581
|View full text |Cite
|
Sign up to set email alerts
|

Judicious Design and Rapid Manufacturing of a Flexible, Mechanically Resistant Liquid‐Like Coating with Strong Bonding and Antifouling Abilities

Abstract: Fluorine‐free liquid‐repellent coatings have been highly demanded for a variety of applications. However, rapid formation of coatings possessing outstanding oil repellency and strong bonding ability as well as good mechanical strength (e.g., bendability, impact resistance, and scratch resistance) remains a grand challenge. Herein, a robust strategy to rapidly create fluorine‐free oil‐repellent coatings in only 30 s via rational design of a semi‐interpenetrating polymer network structure is reported. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…[15a,21,23-26,28] For example, Rabnawaz et al prepared PDMS brush coatings by copolymerization of embedded PDMS-COCl chains and polyurethane substrates. [15a] By rationalizing the PDMS-OH semi-interpenetrating polymer network structure, Lai et al produced a flexible, mechanically resistant liquid-like coating with strong adhesive and antifouling capabilities in just 30 s. [29] Based on the copolymerization method, PDMS brush coatings can be fabricated on a wide variety of substrates including glass, paper, wood, metal, ceramics, and so on. Meanwhile, the fabrication method can be carried out through diverse routes such as dip coating, spraying, and spin coating, indicating that this strategy has a wide range of application.…”
Section: The Methods Of "Copolymerization"mentioning
confidence: 99%
“…[15a,21,23-26,28] For example, Rabnawaz et al prepared PDMS brush coatings by copolymerization of embedded PDMS-COCl chains and polyurethane substrates. [15a] By rationalizing the PDMS-OH semi-interpenetrating polymer network structure, Lai et al produced a flexible, mechanically resistant liquid-like coating with strong adhesive and antifouling capabilities in just 30 s. [29] Based on the copolymerization method, PDMS brush coatings can be fabricated on a wide variety of substrates including glass, paper, wood, metal, ceramics, and so on. Meanwhile, the fabrication method can be carried out through diverse routes such as dip coating, spraying, and spin coating, indicating that this strategy has a wide range of application.…”
Section: The Methods Of "Copolymerization"mentioning
confidence: 99%
“…In nature, there are many examples of superhydrophobic surfaces possessing this special self-cleaning property such as butterfly wings, shark skin, and lotus leaves. It is revealed that this property of the lotus leaf or the “Lotus effect” results from the rough morphology and the hydrophobic epicuticular wax covering the entire surface leaf. Inspired by this discovery, many researchers have mimicked the “Lotus effect” by designing and fabricating artificial superhydrophobic surfaces using the combination of micro/nano or hierarchical morphologies and low surface energy materials. However, besides the elemental factors constituting the superhydrophobicity of a surface-like surface roughness and hydrophobic material coating, the superhydrophobic surface has to be transparent for applications requiring high optical transmittance like solar cell panel protection . Therefore, several strategies for fabricating flexible transparent superhydrophobic structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…14−17 However, besides the elemental factors constituting the superhydrophobicity of a surface-like surface roughness and hydrophobic material coating, the superhydrophobic surface has to be transparent for applications requiring high optical transmittance like solar cell panel protection. 18 strategies for fabricating flexible transparent superhydrophobic structures have been reported. One strategy is to create micro, nano, or hybrid scaled textures on the intrinsic hydrophobic materials by soft lithography, 19 photolithography, 20 or chemical etching 21 technique.…”
Section: Introductionmentioning
confidence: 99%
“…Among published works, there are two kinds of omniphobic surfaces: slippery liquid-infused porous surfaces (SLIPSs) and liquid-like complete solid surfaces. By immersing low-surface tension liquids into the porous materials, a liquid film forms on the surface and hence repels contaminating liquids. , However, low-surface-tension liquids are easily consumed during use, resulting in poor durability. Most of the reported complete solid omniphobic coatings used poly­(dimethylsiloxane) (PDMS)-based chemicals to provide low surface tension. , Inspired by SLIPSs, silicone oil-like PDMS chains are enriched on the surface to build a liquid-like surface that prominently facilitates antifouling performance. ,,, , The surface-enriched, flexible PDMS chains allow the liquid droplets to slide easily in a loose liquid-to-liquid contact, showing a low sliding angle.…”
Section: Introductionmentioning
confidence: 99%